CHARACTERISTICS OF FORMATION OF PROFESSIONAL MOTIVATION OF STUDENTS - Muqaddas Qaxramonovna Raxmanova (Western European Studies, 2024)
Article describes the psychological aspects and motives of students' occupational choice. The author notes that scientific advances in vocational orientation and the use of various techniques help student students change attitudes toward their chosen profession.
Keywords: Motivation of the students; effectiveness of the future profession; the guide position